2009
DOI: 10.1021/jp909211x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of HN3

Abstract: The two-channel thermal decomposition of hydrogen azide, HN(3), was studied computationally. The reaction produces triplet or singlet NH and N(2). A model of the reaction was created on the basis of the theoretical study of the reaction potential-energy surface and microscopic reaction rates by Besora and Harvey (Besora, M.; Harvey, J. N. J. Chem. Phys. 2008, 129, 044303) and the experimental data on the energy-dependent rate constants reported by Foy et al. (Foy, B. R.; Casassa, M. P.; Stephenson, J. C.; King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The thermal decomposition of HN 3 has been studied in the past both experimentally , and computationally. , The experimental efforts were limited to dilute HN 3 in argon, thus, the applicability of their results is limited to the gas phase. In accordance with our DFT calculations, the more favorable unimolecular decomposition channel, namely, the one with the lowest barrier (Δ E r = 16.39 kcal/mol) is the spin-forbidden channel forming the triplet 3 NH, in agreement with literature. , ReaxFF HN3 was trained to reproduce the energy barrier of the lowest energy route (i.e., the spin-forbidden channel).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The thermal decomposition of HN 3 has been studied in the past both experimentally , and computationally. , The experimental efforts were limited to dilute HN 3 in argon, thus, the applicability of their results is limited to the gas phase. In accordance with our DFT calculations, the more favorable unimolecular decomposition channel, namely, the one with the lowest barrier (Δ E r = 16.39 kcal/mol) is the spin-forbidden channel forming the triplet 3 NH, in agreement with literature. , ReaxFF HN3 was trained to reproduce the energy barrier of the lowest energy route (i.e., the spin-forbidden channel).…”
Section: Resultsmentioning
confidence: 99%
“…The thermal decomposition of HN 3 has been studied in the past both experimentally , and computationally. , The experimental efforts were limited to dilute HN 3 in argon, thus, the applicability of their results is limited to the gas phase. In accordance with our DFT calculations, the more favorable unimolecular decomposition channel, namely, the one with the lowest barrier (Δ E r = 16.39 kcal/mol) is the spin-forbidden channel forming the triplet 3 NH, in agreement with literature. , ReaxFF HN3 was trained to reproduce the energy barrier of the lowest energy route (i.e., the spin-forbidden channel). Kajimoto et al and Knyazev et al analyzed the kinetics of secondary reactions in shock tube experiments and identified several possible decomposition and recombination reactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations